Effect of pH and Temperature to Production Antibiotic from Isolate Bacteria Endophytes at Andalas Plant (Morus macroura Miq.) - Yani, Riski Budi; Agustien, Anthoni; Alamsjah, Feskaharny (Metamorfosa: Journal of Biological Sciences; Vol 6 No 1 (2019)DO - 10.24843/metamorfosa.2019.v06.i01.p14, 2019)
The study used survey method and the data were analysed descriptively. The selection of the bacteria which produce antibiotic had been with paper disk method and used Escherichia coli and Staphylococcus aureus as the sample bacteria. This result showed pH 7,0 was succesful optimum pH antibiotic produced for Bacillus sp.1 and Bacillus sp.2. and 37 0 C was the optimum temperature to antibiotic produced from Bacillus sp.1 and Bacillus sp.2.